HYDRONOMY OF THE PRUT WATER CATCHMENT AREA. LEFT RIVER TRIBUTARIES SUMMARY - Anatol EREMIA (Academy of Sciences of Moldova, 2014)
The article deals with issues of the zone hydronymy, having as object of study the names of rivers, Prut left tributaries. The geometric and the geomorphologic characteristics of the aquatic objects are presented. Based on the land toponymic surveys and the cartographic works there are set the limits of the researched hydronym area. There are analyzed the lexical and structural-derivative peculiarities of the hydronyms. There is emphasized the importance of the hydronyms research for the experts from the adjacent scientifi c fi elds (linguistics, geography, history, ethnology, sociology, etc.).